A Chechen al-Qaeda? Caucasian groups further internationalise the Syrian struggle - Guido Steinberg (Stiftung Wissenschaft und Politik (SWP), 2014)
In April 2014 government forces defeated a rebel offensive in the north of the Syrian province of Latakia. Although they initially reached the coast, the insurgents were unable to hold their positions there. The rebel forces included many Chechens and other Caucasians, had who previously been seen fighting exclusively in the Caucasus. Their strong presence in Syria is a completely new turn in international jihadism, and a warning to be taken seriously, as many arrive from the Georgian, Turkish and European diasporas rather from their original home republics. While their goal remains to "liberate" the Caucasus from Russian rule, they are now struggling to topple the regime of Bashar al-Assad in Syria and there is a risk that they will continue terrorist activity after returning to Turkey and Europe. The arrival of the Chechens in Syria makes a joint anti-terrorism strategy with Turkey even more urgent, and forces Western states to cooperate with Russian security agencies. (SWP Comments)
Keywords: 320